The L-shape search method for triobjective integer programming - Boland, Natashia; Charkhgard, Hadi; Savelsbergh, Martin (Mathematical programming computation, 2016)
We present a new criterion space search method, the L -shape search method, for finding all nondominated points of a triobjective integer program. The method is easy to implement, and is more efficient than existing methods. Moreover, it is intrinsically well-suited for producing high quality approximate nondominated frontiers early in the search process. An extensive computational study demonstrates its efficacy.